2020
DOI: 10.1002/cctc.202000725
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Origins of Product Selectivity of Au‐Catalyzed Coupling Benzisoxazoles with Ynamides: A Computational Study

Abstract: Au(I)-catalyzed coupling of benzisoxazoles and ynamides was recently reported to synthesize challenging indoloquinoline core structures. In this report, we employed DFT methods to elucidate the mechanistic details of this reaction. The results reveal that the catalytic cycle involves initial coupling of ynamide with benzisoxazole, simultaneous ring opening of the isoxazole unit and attack of the dimethoxybenzene (DMOB) unit to gold carbenoid, proton transfer from the DMOB group to hydroxyl group, thioether mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Ramana and co‐workers utilized 1,2‐benzo[d]isoxazoles for effective trapping of α‐oxo gold carbenes (generated from 2‐alkynylnitrobenzenes) with a Au(I) catalyst leading to the formation of functionalized quinazoline 1‐oxide [113b] . In 2021, Li and co‐workers studied mechanism and origin of product selectivity of Au‐catalyzed coupling benzisoxazoles with ynamides by carrying out detailed DFT studies and they observed ligand controlled product selectivity by the calculations [114a] …”
Section: Transformations Of Isoxazoles Via Tm‐catalyzed Ring Opening ...mentioning
confidence: 99%
“…Ramana and co‐workers utilized 1,2‐benzo[d]isoxazoles for effective trapping of α‐oxo gold carbenes (generated from 2‐alkynylnitrobenzenes) with a Au(I) catalyst leading to the formation of functionalized quinazoline 1‐oxide [113b] . In 2021, Li and co‐workers studied mechanism and origin of product selectivity of Au‐catalyzed coupling benzisoxazoles with ynamides by carrying out detailed DFT studies and they observed ligand controlled product selectivity by the calculations [114a] …”
Section: Transformations Of Isoxazoles Via Tm‐catalyzed Ring Opening ...mentioning
confidence: 99%